Adjective Collocations in Gurit Bocah of Belik Magazine: Form and Lexical Meaning - Alya, Nanda Nursa; Winarti, Daru (Anaphora : Journal of Language, Literary, and Cultural Studies, 2025)
This study highlights the importance of examining children’s language use in Javanese literary media as an indicator of language mastery and development. Focusing on the Gurit Bocah section of Belik magazine, this research investigates adjective collocations produced by children by examining their morphological forms and lexical meanings. The data were analyzed using distributional and referential methods. The findings reveal that children predominantly use monomorphemic adjectives, while polymorphemic forms appear through affixation, reduplication, and a combination of compounding and reduplication, totaling fourteen identified forms. In terms of collocation, adjectives consistently combine with multiple nouns and form systematic patterns. These patterns are classified into four semantic groups: (1) physical and natural environment, (2) feelings and mental conditions, (3) values and evaluations, and (4) activities and states. These findings indicate that children’s adjective use in Javanese literary texts is systematic rather than random, reflecting both morphological competence and lexical–semantic awareness shaped by their experiential world and the literary context of Belik magazine.